2021
DOI: 10.3389/fimmu.2020.619872
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Functions of γδ T Cells in the Progression of Hepatitis B Virus and Hepatitis C Virus Infection

Abstract: Hepatitis B virus (HBV) and hepatitis C virus (HCV) infections are primary risk factors for a wide spectrum of liver diseases that severely affect human health. The liver is an immunological organ that has an abundance of immune cells. Thus, various innate or adaptive immune cells are involved in the progression of HBV or HCV infection. Among those cells, a unique kind of immune cell, the γδ T cell, contributes to promoting or inhibiting the progression of liver diseases. To reveal the diverse roles of γδ T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…γδT cells are named after their TCR, which is made of a γ- and δ-chain [ 68 ]. Different γδ TCRs recognize specific sets of antigens that are not clearly defined yet [ 69 ].…”
Section: The Hepatic Immune Environmentmentioning
confidence: 99%
“…γδT cells are named after their TCR, which is made of a γ- and δ-chain [ 68 ]. Different γδ TCRs recognize specific sets of antigens that are not clearly defined yet [ 69 ].…”
Section: The Hepatic Immune Environmentmentioning
confidence: 99%
“…35 Furthermore, some studies have shown that the livers of HCVinfected patients are rich in γδ T-cell recruitment. 36,37 These recruited γδ T cells are mainly Vδ 1 + γδ T-cells that produce higher levels of IFN-γ and likely exacerbate HCV-induced hepatitis. 36,37 According to another study, HCV infection enhances cytotoxicity of γδ T-cells to hepatocytes, thereby aggravating liver injury 38 ; however, it was noted that peripherally activated Vγ 9 Vδ 2 T cells in humans were associated with significantly reduced HCV RNA levels.…”
Section: γδ T Cells and Experimental/acute Liver Failurementioning
confidence: 99%
“…Furthermore, some studies have shown that the livers of HCV‐infected patients are rich in γδ T‐cell recruitment 36,37 . These recruited γδ T cells are mainly Vδ 1 + γδ T‐cells that produce higher levels of IFN‐γ and likely exacerbate HCV‐induced hepatitis 36,37 .…”
Section: γδ T Cells and Viral Hepatitismentioning
confidence: 99%
See 1 more Smart Citation
“…γδ T Vδ1 + liver lymphocytes have been described as necessary for the effective antitumor response in a TNF- and IFN-γ−dependent manner [ 219 ]. Such γδ T lymphocyte populations have been associated with immunogenic responses in HCV infection [ 220 , 221 , 222 ]. In plasmodium infection, γδ T lymphocytes were also described as having an important protective role [ 223 , 224 ].…”
Section: Introductionmentioning
confidence: 99%